Black landscapes matter - Hood, Walter, 1958-; Tada, Grace Mitchell (University of Virginia Press, 2020)
"Black Landscapes Matter probes the very timely issue of how race, memory, and meaning intersect in the American landscape. The book provides examples of how African American landscapes are rejected and erased in a variety of places across the US--from Charlotte, NC, to New Orleans, LA, Detroit, MI, and Milwaukee, WI--along with calls to action"--